The Community Development Process in the Climate Village Programme through the Biopore Programme in Blawi Village, Lamongan - Imam Sakroni; Muhammad Choirul Mustofa; Salwa Nabilah (Program Studi Teknik Sipil, Fakultas Teknik, Universitas Islam Lamongan, 2023)
Development activities always cause environmental damage and/or pollution. This development triggers the acceleration of the phenomenon of climate change which should be a natural phenomenon. This research aims to empower the community with a community development process which consists of the stages of program planning, planning, implementation, evaluation & results of changes, and termination. The community development process was carried out using a qualitative approach and case studies in the field involving 3 informants consisting of the Blawi Village government, Karang Taruna, and the Blawi Village community who were directly involved in the Biopori Program and the Clean Village Program. The selection of informants was carried out to dig deeper into community development in the Biopori Program and the Clean Village Program. Biopori is a simple technology that can increase rainwater absorption and the amount of clean water reserves in the ground during flood control efforts. Clean Village is a simple tool to increase public awareness of the importance of clean houses for public health and flood control efforts in Blawi village. The result of this activity was the planting of biopori, the installation of 40 biopori holes in each community unit in Blawi Village was carried out as a pilot to be developed and carried out by the residents themselves.